IBM Bagi Siswa Kelas XI SMK Teknik Kenderaan Ringan Di SMK Negeri 1 Sei Rampah Kabupaten Serdang Bedagai - J, Junaidi; Ritonga, Din Aswan Amran (LPPM STIKOM Tunas Bangsa, 2019)
State Vocational School 1 Sei Rampah Serdang Bedagai Regency annually holds Competency Exams for Class XII Lightweight Vocational School, prior to conducting the National Examination. Every year almost 90% fail in the Competency Exams conducted by these students. Therefore we are from Faculty of Engineering and Computer teaching staff serve this Vocational School to hold Competency Test Training for Class XI Students, so as not to fail when they later in class XII, to carry out competency tests. As for the implementation of competency training are: Tune up competency test training, Electricity, Steering System, Over Hole Engine and chassis.